The comparison of Lithuanian texts’ styles by using the statistical analysis of the universal quantitative characteristics - Piaseckienė, Karolina; Radavičius, Marijus; Stiklius, Raimundas (Lietuvos matematikos rinkinys, 2010)
Lithuanian language is quite complex and flexible, and its significantly complicates the development of efficient algorithms for the automatic processing of Lithuanian texts. For studying text-styles features were selected the universal quantitative characteristics that are unrelated to the text content and can be calculated for any text. This article shows how mathematical Statistics can help to distinguish and interpret the Lithuanian language styles. Studies of the log-linear models show the connection between the letters and sounds structure and the scientific and fiction.